A multi-chromic supercapacitor of high coloration efficiency integrating a MOF-derived V2O5 electrode. Issue 46 (16th November 2022) - Dewan, Anweshi; Narayanan, Remya; Thotiyl, Musthafa Ottakam
Abstract : Multichromic energy storage devices improve human–machine interfacing. Here, MOF-derived V2 O5 is integrated as a negative electrode in a multi-colored electrochromic supercapacitor assembly along with electrochromic PANI as the positive electrode. Abstract : Modern technological trends in smart electronic devices demand more intelligent automation. Simultaneous integration of energy storage and multicolor electrochromism in a single device improves user–device interfacing based on a salient human-readable output. In this work, primarily metal–organic framework (MOF) derived V2 O5 was synthesized which, as an electrochromic material, shows high optical modulation of 35% at 485 nm, with very fast switching speeds (2.9/3.4 s for coloring/bleaching). The multiple coloration states of the V2 O5 electrode make it worthy for further integration as a smart negative electrode in a multicolored electrochromic asymmetric supercapacitor, where the electrochromic polyaniline electrode serves as the counter electrode. The device demonstrates a high coloration efficiency of 137.2 cm 2 C −1 and an areal capacitance of 12.27 mF cm −2 and an energy density of 2.21 × 10 −3 mW h cm −2 at a current density of 0.05 mA cm −2 . By virtue of its different chromatic states during charging and discharging, smart visual tracking of the state of charge of the supercapacitor can be realized. Such a design of energy storage devices will have promising practical application in futuristic smart multifunctional electronic devices.